Wild corvid birds colonized with vancomycin-resistant Enterococcus faecium of human origin harbor epidemic vanA plasmids - Oravcová, Veronika; Peixe, Luísa; Coque, Teresa M; Novais, Carla; Francia, Maria V; Literák, Ivan; Freitas, Ana R (Environment international, 2018)
The most prevalent type of acquired vancomycin resistance in Enterococcus faecium (VREfm) is encoded by the vanA transposon Tn1546, mainly located on transferable plasmids. vanA plasmids have been characterized in VREfm from a variety of sources but not wild birds. The aim of this study was to analyse the genetic context of VREfm strains recovered from wild corvid birds and to compare their plasmid and strain characteristics with human strains. To achieve that, 75 VREfm isolates, including strains from wild birds recovered during wide surveillance studies performed in Europe, Canada and the United States (2010-2013), and clinical and wastewater strains from Czech Republic, a region lacking data about vanA plasmids, were analysed. Their population structure, presence of major putative virulence markers and characterization of vanA transposons and plasmids were established. VREfm from wild birds were mainly associated with major human lineages (ST18 and ST78) circulating in hospitals worldwide and were enriched in putative virulence markers that are highly associated with clinical E. faecium from human infections. They also carried plasmids of the same families usually found in the clinical setting [RCR, small theta plasmids, RepA_N (pRUM/pLG1) and Inc18]. The clinically widespread IS1251-carrying Tn1546 type "F" was predominant and Tn1546-vanA was mainly located on pRUM/Axe-Txe (USA) and Inc18- or pLG1-like (Europe) plasmids. VREfm from hospitals and wastewaters carried Tn1546-vanA in different plasmid types including mosaic pRUM-Inc18 plasmids, not identified in wild birds. This is the first characterization of vanA plasmids obtained from wild birds. A similar plasmid pool seems to exist in different clonal E. faecium backgrounds of humans and wild birds. The isolation of VREfm strains from wild birds that belong to human E. faecium adapted lineages and carry virulence genes, Tn1546 and plasmid variants widespread in the clinical setting is of concern and highlight their role as potential drivers of the global dissemination of vancomycin resistance.
Keywords: Animals; grampozitivní bakteriální infekce; Zoonoses; Passeriformes; lidé; Plasmids; zvířata; Vancomycin Resistance; zoonózy; Gram-Positive Bacterial Infections; plazmidy; Vancomycin-Resistant Enterococci; enterokoky rezistentní vůči vankomycinu; rezistence na vankomycin; Enterococcus faecium; Humans